New Technique use to differentiate between Pseudo and true coagulase Activity of Staphylococcus aureus isolated from Different infected Sites in Patients from Baghdad Hospitals - Mohammed kadum Al-Araji (College of Pharmacy / Mustansiriyah University, 2012)
A total of 300 strains of Staphylococci isolated from various pathological sites of infection from different hospitals; these specimens derived from cases of human infections were tested for staphylocoagulase activity. Test systems employing normal citrated rabbit plasma and the same substrate supplemented with inhibitors of thrombin and proteolytic enzymes (but not influencing the staphylocoagulase activity) were used for testing suspensions of bacteria and cell-free culture supernatants. A total of 200 strains clotted normal rabbit plasma; however addition of Trasylol and heparine resulted in positive results in 100 strains, whereas plasma supplemented with Trasylol and hirudin was coagulated definitely by only 70 strains.It is postulated that proteolytic enzymes of staphylococci interfere with staphylocoagulase-induced clotting and may simulate coagulase-positve activity of staphylococci.To avoid such false results, attest system for detection of sse shtaphylocoagulaould include proteolytic enzyme inhibitors The purpose of this investigation was to verify this hypothesis by testing a collection of staphylococci strains from different sources of infections against rabbit plasma in atypical coagulase test versus the same supplemented with specific inhibitors of proteases and thrombin depending on the sever sites of infections.